Geología de los cuadrángulos de Teniente Pinglo, Santa María de Nieva, Puerto Alegría y Puerto América. Hojas: 9-h, 10-h, 9-i y 10-i - [Boletín A 99] - Quispesivana Quispe, Luis Juan (1997)
185 p., 4 mapas